Pendampingan Digitalisasi Arsip Melalui Metode In – On – In untuk Meningkatkan Kemampuan Tenaga Administrasi Sekolah (TAS) dalam Pelestarian Arsip - Pandit Isbianti; Latifah Nur Arbaatun; Eka Bintang; Dwi Nur Cahyaning; Nur Chanabillah (Universitas Negeri Yogyakarta, 2021)
Abstrak: Penelitian ini bertujuan untuk menggali proses pendampingan digitalisasi arsip berikut dampaknya bagi Tenaga Administrasi Sekolah (TAS). Tenaga administrasi sekolah bertugas memberikan layanan administrasi sekolah dalam hal urusan kepegawaian, keuangan, sarana prasarana, humas, persuratan dan kearsipan, kesiswaan, kurikulum, dan administrasi umum. Kegiatan administrasi tersebut akan bermuara pada terciptanya arsip sebagai asset sekolah yang harus dilestarikan. Sayangnya, kemampuan TAS dalam melestarikan arsip masih kurang dikarenakan ketidak sesuaian latar belakang pendidikan dengan bidang tugas dan minimnya kegiatan peningkatan kompetensi pengelolaan arsip. Sehubungan dengan hal tersebut, dilakukanlah pendampingan digitalisasi arsip melalui metode In-on_in untuk meningkatkan kemampuan TAS dalam pelestarian arsip. Penelitian ini merupakan penelitian kualitatif dengan sumber data tenaga administrasi sekolah. Hasil penelitian ini mencakup proses pendampingan yang meliputi in the job training 1, on the job training dan in the job training 2 serta dampak kegiatan pendampingan berupa meningkatnya kemampuan TAS dalam pelestarian arsip. Assistance in Archive Digitization Through The In-On-In Method to Improve The Ability of School Administration Personnel (TAS) in Archive PreservationAbstract: This study aims to explore the process of assisting archive digitization and its impact on School Administration Staff (TAS). School administration staff are tasked with providing school administrative services in terms of personnel affairs, finance, infrastructure, public relations, correspondence and archives, student affairs, curriculum, and general administration. These administrative activities will lead to the creation of archives as school assets that must be preserved. Unfortunately, TAS 'ability to preserve archives is still lacking due to the incompatibility of educational background with the field of work and the lack of activities to increase archive management competence. In connection with this, assistance was carried out on digitizing archives through the method In-on-in to improve TAS ability to preserve archives. This research is qualitative research with data sources of school administration staff. The results of this study include the mentoring process which includes in the job training 1, on the job training and in the job training 2 as well as the impact of mentoring activities in the form of increasing TAS ability to preserve archives.